MODELING USERS’ ATTITUDES TOWARD ERP SYSTEMS WITH A BAYESIAN NETWORK - Kao, Han-Ying; Hsu, Chu-Ling (International Journal of Industrial Engineering: Theory, Applications and Practice, 2011)
<span style="font-size: 10pt; font-family: ";Times New Roman";; mso-fareast-font-family: CMR12; mso-bidi-font-size: 12.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-TW; mso-bidi-language: AR-SA;" lang="EN-US">This study proposes a robust approach, Bayesian networks, in developing marketing knowledge bases of users’ attitudes toward ERP systems. Using the Bayesian network, the factors and their interrelationship will be modeled compactly in graphical as well as numerical levels. This work first identifies the factors influencing the decision on ERP systems implementation. Next, based on these factors the questionnaires to investigate users’ attitudes towards ERP systems are designed, which are further analyzed for the structure of the Bayesian network. Third, the parameters of the Bayesian network are learned and tested. Finally, this paper demonstrates how Bayesian networks support prediction and actions in ERP system marketing. This paper aims to propose the knowledge model in ERP software industry, which facilitates marketing strategy generation.